Patterns and history of prescription drug use among opioid-related drug overdose cases in British Columbia, Canada, 2015–2016. (1st January 2019) - Smolina, Kate; Crabtree, Alexis; Chong, Mei; Zhao, Bin; Park, Mina; Mill, Christopher; Schütz, Christian G.
Highlights: Most people did not have a prescription for an opioid for pain when they overdosed. Half of cases had no opioid for pain prescriptions in past five years before overdose. Prescriptions for psychoactive medications were common among people who overdosed. Current or past use of medications to treat opioid use disorder was uncommon. Regulation of prescribing may have limited short-term impact on the current opioid crisis. Abstract: Background: British Columbia is the epicenter of the current fentanyl-related overdose crisis in Canada. Our study characterizes prescribing histories of people who had an opioid-related overdose compared to matched controls. Methods: We examined linked administrative data for individuals who overdosed between January 1, 2015 and November 30, 2016. Past prescriptions over five years were assessed for opioids for pain, opioid agonist therapy, benzodiazepines/z-drugs, antidepressants, antipsychotics, gabapentinoids, mood stabilizers and anti-epileptics, muscle relaxants, and other sedating medications. Prescribing history of 9964 cases was compared with that of 49, 820 matched controls. Results: Overdose cases were more likely to be prescribed opioids for pain and to have used prescription opioids on a long-term basis in the previous five years compared to controls. However, at the time of overdose, 92% of men and 86% of women did not have an active opioid for pain prescription, and approximately half had not filled one in the past five years. Those who overdosed tended to have more prescriptions for psychotropic substances than controls. Fewer than 10% of cases had an active prescription for opioid agonist therapy and most were not on treatment in the past. Conclusions: Low prevalence of active prescriptions for opioids for pain at the time of overdose suggests that opioid prescribing plays a limited short-term impact in the current fentanyl-related crisis of overdoses. While liberal opioid prescribing practices may have contributed to the development of the current overdose crisis, regulation and enforcement of clinicians' prescribing practices will likely have limited impact in reducing overdoses.